2021
DOI: 10.1186/s13018-021-02772-0
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of osteoporosis in the world: a comprehensive systematic review and meta-analysis

Abstract: Background Osteoporosis affects all sections of society, including families with people affected by osteoporosis, government agencies and medical institutes in various fields. For example, it involves the patient and his/her family members, and government agencies in terms of the cost of treatment and medical care. Providing a comprehensive picture of the prevalence of osteoporosis globally is important for health policymakers to make appropriate decisions. Therefore, this study was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
210
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 442 publications
(280 citation statements)
references
References 81 publications
6
210
3
4
Order By: Relevance
“…Based on a meta-analysis conducted worldwide and reviewing 86 studies with a sample size of 103,334,579 in the age range of 15 to 105 years, it was reported that the prevalence of osteoporosis in the world is 18.3% [ 68 ], which shows a high prevalence, while age is a high-risk factor for osteoporosis and Vitamin D insufficiency and reduced calcium absorption are common in the elderly [ 69 , 70 ]. Osteoporosis is increasing due to increased life expectancy and an aging population [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a meta-analysis conducted worldwide and reviewing 86 studies with a sample size of 103,334,579 in the age range of 15 to 105 years, it was reported that the prevalence of osteoporosis in the world is 18.3% [ 68 ], which shows a high prevalence, while age is a high-risk factor for osteoporosis and Vitamin D insufficiency and reduced calcium absorption are common in the elderly [ 69 , 70 ]. Osteoporosis is increasing due to increased life expectancy and an aging population [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein we have prepared cAp and cAp-Tb nanoparticles and investigated their loading/release ability of DF, a potent non-steroidal antiinflammatory drug, using both nanocarriers in different conditions, and we have analyzed their cytocompatibility as well as their biological activities in an in vitro human osteoblast inflammation model. Indeed, today bone tissue pathologies, such as osteoporosis, osteoarthritis, rheumatoid arthritis represent important health problems with considerable socio-economic burden, linked to the general population aging [ 8 , 9 ] and are all characterized by a clinical condition of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…From the other side, also the nature/composition of the nanocarrier can vary depending on the diseases to be treated. Today bone tissue pathologies, such as osteoporosis, osteoarthritis and rheumatoid arthritis represent important health problems with considerable socio-economic burden, linked to the general population aging [ 8 , 9 ]. These musculo-skeletal disorders are characterized by a clinical condition of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…By 2050, hip fractures may exceed 21 million cases [1]. The prevalence of osteoporosis is 18.3% globally, and it is greater in women than in men (23.1 and 11.7, respectively) [4]. The direct cost of treating these osteoporotic fractures in five European countries (France, Germany, the United Kingdom, Italy and Spain) is EUR 29 billion, while for the 27 EU Member States as a whole it is EUR 38.7 billion, a cost that is expected to increase by 25% until 2025 [5].…”
mentioning
confidence: 99%